2022
DOI: 10.1159/000527332
|View full text |Cite
|
Sign up to set email alerts
|

The Obesity Paradox in Heart Failure: Is It Still Valid in Light of New Therapies?

Abstract: Background: Obesity increases the risk of cardiovascular disease and heart failure (HF). However, in patients with established HF, many studies observed greater survival with increasing adiposity. This counterintuitive observation has been termed the “obesity paradox”. In recent years, new HF therapies have emerged that improve prognosis in patients with HF. Some of these, such as sodium-glucose cotransporter 2 inhibitors (SGLT2i), cause weight loss and may therefore interfere with the obesity paradox. Summary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 123 publications
0
5
0
Order By: Relevance
“…Obesity is prevalent among HF patients, but whether it can serve as an independent prognostic factor for HF outcomes remains a topic of debate [21]. Some relevant studies have suggested that overweight and mildly to moderately obese HF patients may have longer survival rates than normal-weight or underweight HF patients [22,23]. The potential explanation for this difference may be related to whether fat leads to excessive accumulation of WAT and myocardial fat infiltration [24,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Obesity is prevalent among HF patients, but whether it can serve as an independent prognostic factor for HF outcomes remains a topic of debate [21]. Some relevant studies have suggested that overweight and mildly to moderately obese HF patients may have longer survival rates than normal-weight or underweight HF patients [22,23]. The potential explanation for this difference may be related to whether fat leads to excessive accumulation of WAT and myocardial fat infiltration [24,25].…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesized that, compared to BMI, EAT might be a more precise indicator of obesity, and thus, measuring EAT could better assess disease progression. In fact, previous research has confirmed that EAT participates in the occurrence and progression of cardiovascular diseases by synthesizing and secreting proinflammatory mediators and neurohormones such as IL-1β, IL-6, TNF-α, MCP-1, resistin, visfatin, and others [23]. Currently, research on EAT in HF patients is primarily focused on those classified based on ejection fraction (EF) [26].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies performed in the last two decades consistently showed that mild to moderate obesity-even if associated with increased risk for cardiovascular diseases and all-cause mortality in healthy subjects-prevents early death in chronic HF. This phenomenon has also been shown for a plenty of other cardiovascular disease conditions and is termed the 'obesity paradigm' (35,36). It has been clearly shown that muscle wasting/sarcopenia, which affects 20%-50% of patients with chronic HF including patients in young age groups, even before a reduction in total body weight sets in, relates with impaired exercise tolerance, quality of life and mortality (33,(37)(38)(39).…”
Section: Clinical Data Regarding Locomotor Muscle Dysfunction In Hf H...mentioning
confidence: 90%
“…Even though obesity is highly prevalent in HFpEF and seems to be of causative impact at least in a subset of HFpEF patients with a distinct obesity phenotype, the so called obesity paradigm indicating higher mortality in patients with lower BMI has been shown consistently in different HFpEF populations ( 36 , 40 42 ). Recently, this was confirmed in a secondary analysis of the DELIVER trial analyzing safety and efficacy of the SGLT2 inhibitor dapagliflozin vs. placebo in 6,263 patients with HFpEF according to baseline BMI.…”
Section: Influence Of Hf On Locomotor Musclesmentioning
confidence: 99%
“…Consistent results were seen in small Japanese populations, although the cutoff for the definition of obesity (BMI >25 kg/m 2 ) varied. This phenomenon, widely known as the “obesity paradox,” implies that a higher BMI is associated with a better prognosis for patients with HF [4].…”
mentioning
confidence: 99%